2005
DOI: 10.1007/978-3-540-32260-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating Teams in Uncertain Environments: A Hybrid BDI-POMDP Approach

Abstract: Abstract. Distributed partially observable Markov decision problems (POMDPs) have emerged as a popular decision-theoretic approach for planning for multiagent teams, where it is imperative for the agents to be able to reason about the rewards (and costs) for their actions in the presence of uncertainty. However, finding the optimal distributed POMDP policy is computationally intractable (NEXPComplete). This paper is focussed on a principled way to combine the two dominant paradigms for building multiagent team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…4 Following, we internalized the regulation mechanism in the agents, through a BDI-POMDP hybrid model [38], going toward the self-regulation of social exchanges. A comparison between social exchange regulation models was also presented by Pereira et al [40] Observe that hybrid models have been proposed in the literature in order to take advantages of both POMDPs and BDI architecture (see, e.g., [33,34,37,[51][52][53][54][55]). 5 Simari and Parsons [53] showed that the plans derived from an optimal policy are exactly the same adopted by a BDI agent that selects plans with the highest utility, and that operate with an optimal reconsideration strategy.…”
Section: Previous Work On the Regulation Of Strategy-based Social Excmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Following, we internalized the regulation mechanism in the agents, through a BDI-POMDP hybrid model [38], going toward the self-regulation of social exchanges. A comparison between social exchange regulation models was also presented by Pereira et al [40] Observe that hybrid models have been proposed in the literature in order to take advantages of both POMDPs and BDI architecture (see, e.g., [33,34,37,[51][52][53][54][55]). 5 Simari and Parsons [53] showed that the plans derived from an optimal policy are exactly the same adopted by a BDI agent that selects plans with the highest utility, and that operate with an optimal reconsideration strategy.…”
Section: Previous Work On the Regulation Of Strategy-based Social Excmentioning
confidence: 99%
“…For that, we have built on hybrid BDI-POMDP agent models, defined over the BDI (Beliefs, Desires, Intentions) architecture [5,43,56] with plans derived from POMDP (Partially Observable Markov Decision Processes) [30] models of social exchange strategies, in the line of the works of Simari and Parsons [53] and other authors [33,34,37,51,52,54,55].…”
Section: Introductionmentioning
confidence: 99%